2015
DOI: 10.1002/pola.27651
|View full text |Cite
|
Sign up to set email alerts
|

A new route to atactic polypropylene: The second life of premetallocene homogeneous polymerization catalyst

Abstract: Amorphous atactic polypropylene (PP) with an average molecular weight of 50,000-100,000 is produced by polymerizing propylene with a ternary Ti(Oiso-Pr) 4 -AlEt 2 Cl/MgBu 2 catalyst at 30-50. Main advantages of this catalyst compared with other catalysts capable of nearly exclusively producing atactic PP (such as some heterogeneous Ziegler-Natta, metallocene and postmetallocene catalysts) are high activity, low cost and the ease of use: the catalyst is prepared in situ from three commercially available compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…The position of each signal and the relative contents of stereo-sequences are listed in Table 6. The 13 C NMR data suggest that this fraction mostly has a head-to-tail structure [21]; the T αγ and T βγ signals of regio-errors at about 38 and 31 ppm [22] are fairly low. The polymer is almost atactic: it contains all the possible stereosequences in comparable amounts.…”
Section: Molecular-mass Heterogeneity and Compositional Heterogeneitymentioning
confidence: 90%
See 1 more Smart Citation
“…The position of each signal and the relative contents of stereo-sequences are listed in Table 6. The 13 C NMR data suggest that this fraction mostly has a head-to-tail structure [21]; the T αγ and T βγ signals of regio-errors at about 38 and 31 ppm [22] are fairly low. The polymer is almost atactic: it contains all the possible stereosequences in comparable amounts.…”
Section: Molecular-mass Heterogeneity and Compositional Heterogeneitymentioning
confidence: 90%
“…The Propylene polymerization. It was previously shown that the Ti(O-iso-Pr) 4 -AlEt 2 Cl/MgBu 2 system provides efficient polymerization of propylene [21]; in the case of polymerization in a liquid monomer, the PP yield is ~10 t/mol Ti h ( Table 5). The resulting polymers are characterized by М = (50-100) × 10 3 and a broad MMD.…”
Section: Molecular-mass Heterogeneity and Compositional Heterogeneitymentioning
confidence: 98%
“…The data obtained in this research show that a combination of the oxyquinolinyl Ti complex I and the binary Al(C 2 H 5 ) 2 Cl – Mg(C 4 H 9 ) 2 cocatalyst can be viewed as a typical supported, multicenter post‐metallocene catalyst, similar to catalysts prepared from several other Ti complexes with multidentate ligands …”
Section: Discussionmentioning
confidence: 80%
“…The spectrum of the soluble amorphous fraction [Fig. (B)] is typical for the spectra of amorphous fractions of PP prepared with different post‐metallocene catalysts; it contains numerous signals of pentads and heptads characterizing various types of steric sequences in PP chains . This amorphous fraction has a noticeable prevalence of isotactic sequences (the mmmm signal at −21.3 ppm); its mmmm content is about 30%; it would be merely ∼6% if the material were completely atactic.…”
Section: Resultsmentioning
confidence: 99%
“…The complexes were activated with a binary organometallic cocatalyst Al(C 2 H 5 ) 2 Cl ‐ Mg(C 4 H 9 ) 2 . As we reported earlier, combinations of organoaluminum compounds AlR 2 Cl and organomagnesium compounds MgR′ 2 , when used at an [Al]:[Mg] molar ratio above 2, are universal cocatalysts for all types of transition‐metal polymerization catalysts, including common heterogeneous and supported Ti‐based Ziegler‐Natta catalysts, Ti(OR) 4 ‐type compounds, metallocene complexes, and several post‐metallocene catalysts . These binary cocatalysts are also used for activation of Ni‐ and Ti‐based complexes in alkene oligomerization reactions .…”
Section: Introductionmentioning
confidence: 87%